Synthesis and Characterization of Urea Schiff Base Chelates of Cr(III), Cr(VI), TiO(IV) and Pb(II) - EL-AJAILY, M.M.; EL-SAIED, F.M. (Asian Journal of Chemistry, 2010)
New four Schiff base complexes derived from salicylaldehyde and urea have been prepared and characterized. The elemental analysis data show the formation of 1:1 [M:L] chelates. The molar conductance values of the prepared chelates reveal a non-electrolytic nature. The magnetic moment values exhibit the existence of three unpaired electrons in the Cr(III) chelate and diamagnetic phenomena for the other chelates. The infrared spectral data display the coordination sites of bonding of the Schiff base towards the metal ions under investigation. The electronic spectral data of the Schiff base and its chelates show π→π* (phenyl ring), n→π* (HC=N) and the expected geometrical structures. The electron paramagnetic resonance spectral data satisfy the presence of a paramagnetic phenomena and support the expected geometrical structure of Cr(III) chelate.